Finite element Analysis and biomechanical testing of the new MiniMIS short stem - Trieb, Klemens; Huber, Dominik; Sonntag, Robert; Kretzer, Jan Philippe (Zeitschrift für Orthopädie und Unfallchirurgie, 2019)
INTRODUCTION: In hip arthroplasty a trend towards short stem prostheses is observed. The aim of this study is to investigate the finite element analysis and biomechanical fatigue performance of a new short stem prosthesis. - METHODS: A finite element analysis was used to simulate the stresses during neck and stem loading according to the ISO standards. Numerical analysis with applied forces of up to 6 kN were performed in the vertical direction on a femoral neck-preserving stem (MiniMIS). During experimental testing, 10 million cycles with a maximum load of 5.34 kN using the worst case of a XL ceramic head (36 mm) were applied. This was followed by a Locati test, where the load was increased until failure of the stem. - RESULTS: For all stems, stress values below the limits according to the ISO 5832-3 standard (yield strength of 800 N/mm2) were calculated by the finite element analysis. In the biomechanical tests, the total number of 10 million cycles with a maximum load of 5.34 kN was reached in all cases without any visible signs of implant damage. The estimated load to failure after stem testing was 2.16 kN (required by ISO 7206-4: 1.2 kN) and after neck testing > 9.35 kN (required by ISO 7206-6: 5.4 kN). - SUMMARY: The presented finite element calculation and subsequent biomechanical testing show that the design of this stem meets the essential mechanical requirements given by the ISO and a material failure is not expected in all variants tested under the applied boundary conditions.